Correlation Of Serum Calcium, Phosphorus And 25‑Hydroxy Vitamin D With Glycemic Parameters In Patients With Type 2 Diabetes Mellitus: A Cross‑Sectional Study - T V , Shylaja; A Natikar , Jyothi; Yatoo , Bilal Ahmad; Ahmed , Qazi Rais; Afaq , Nashra; G, Asha; Kumar , Gaurav; Jaiswal, Divya (Journal of Neonatal Surgery, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disorder associated with chronic hyperglycemia and insulin resistance. Mineral metabolism, particularly involving calcium, phosphorus, and vitamin D, may play a pivotal role in T2DM pathophysiology. Aim and Objective: To study the correlation of serum calcium, phosphorus, and vitamin D in type 2 diabetes mellitus patients compared to healthy controls. Materials & Methods: A prospective cross-sectional study was conducted on 160 individuals — 80 diagnosed T2DM patients (cases) and 80 age- and sex-matched healthy individuals (controls). Serum calcium, phosphorus, and 25-hydroxy vitamin D levels were measured using standardized biochemical methods. Data were analyzed using Pearson correlation and chi-square tests. Results: Among 80 diabetic patients, 65% were male and 35% female. Vitamin D deficiency (<20 ng/ml) was present in 21.25% of diabetic patients, and serum calcium was below 8.4 mg/dL in 30% of them. Hypophosphatemia (<3.4 mg/dL) was observed in 72.5% of diabetic patients. All three parameters showed statistically significant differences compared to controls. Conclusion: Diabetic patients exhibited lower levels of serum calcium, phosphorus, and vitamin D. These biochemical markers may serve as early indicators of metabolic dysfunction in T2DM and could have implications for clinical management